Acting autonomously or mimicking the state and peers? A panel tobit analysis of financial dependence and aid allocation by Swiss NGOs - Axel Dreher; Peter Nunnenkamp; Hannes Öhler; Johannes Weisser (Center for Economic Studies and ifo Institute (CESifo), 2009)
NGO aid is still widely believed to be superior to official aid (ODA). However, the incentives of NGOs to excel and target aid to the poor and deserving are increasingly disputed. We contribute to the emerging literature on the allocation of NGO aid by performing panel Tobit estimations for Swiss NGOs. The analysis offers new insights in two major regards: First, we cover the allocation of both self-financed and officially co-financed aid for a large panel of NGOs and recipient countries. Second, by classifying each NGO according to its financing structure, we address the unresolved question of whether financial dependence on the government impairs the targeting of NGO aid. It turns out that NGOs mimic the state as well as NGO peers. Officially refinanced NGOs are more inclined to imitate the allocation of ODA. However, the degree of financial dependence does not affect the poverty orientation of NGO aid and the incentives of NGOs to engage in easier environments. The allocation of self-financed aid differs in several respects from the allocation of officially co-financed aid, including the role of financial dependence for imitating the state and herding among NGOs.
Keywords: F35; 330; NGO aid; aid allocation; official co-financing; financial dependence; Private Entwicklungshilfe; Nichtregierungsorganisation; Finanzierung; Staatliche Einflussnahme; Entwicklungshilfe; Allokation; Agency Theory; Herdenverhalten; Schweiz